'Being Urban' in the Context of Global Urbanization: The Case of India. (August 2016) - Channa, Subhadra Mitra
Western intellectual sources have dominated the social sciences to an extent that most definitions originate from a Eurocentric meaning system; words like urban, wild, nature, and culture being no exception. This paper interrogates and makes a critical assessment of what urban may mean in a non-western context, taking Delhi, the capital of India, as an example. It demonstrates that the meaning of a phrase, 'being urban', can only be understood in its historical, social/cultural, and political context; that the notion of a civil society, and meaning of terms such as public and private may be contextualized in varying moral universes and value systems to mean quite different things in different contexts. Overall the paper seeks to illuminate the futility of monolithic and reductionist constructs and value of situational and ethnographically constructed meanings of social and cultural phenomena. It demonstrates that even dichotomies like urban/non-urban are fuzzy and fluid, given the actual situation of real cities and their population; that a city is not defined by structure alone but by the people who live in it.